2008
DOI: 10.1109/tsp.2007.914311
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Covariance Matrix Estimates in Impulsive Noise

Abstract: This paper deals with covariance matrix estimates in impulsive noise environments. Physical models based on compound noise modeling (SIRV, Compound Gaussian Processes) allow to correctly describe reality (e.g., range power variations or clutter transitions areas in radar problems). However, these models depend on several unknown parameters (covariance matrix, statistical distribution of the texture, disturbance parameters) which have to be estimated. Based on these noise models, this paper presents a complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 29 publications
3
130
0
2
Order By: Relevance
“…Moreover, real fast moving targets, observed by a wideband radar, are both extended and range migrating, as shown in Figure 1, d. However, the detection of extended target is not considered in this study, so we focus on the model shown in Figure 1, b. Finally, in practical applications, the aforementioned detectors exploit CM estimated from the reference cells, resulting in the appropriate change of the threshold [28], [29]. Coming back to the problem of migrating target detection in a highly inhomogeneous clutter, the GLRT for the CompoundGaussian model can be written in the following form:…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, real fast moving targets, observed by a wideband radar, are both extended and range migrating, as shown in Figure 1, d. However, the detection of extended target is not considered in this study, so we focus on the model shown in Figure 1, b. Finally, in practical applications, the aforementioned detectors exploit CM estimated from the reference cells, resulting in the appropriate change of the threshold [28], [29]. Coming back to the problem of migrating target detection in a highly inhomogeneous clutter, the GLRT for the CompoundGaussian model can be written in the following form:…”
Section: Problem Formulationmentioning
confidence: 99%
“…In particular it can influence the number of iterations required for convergence. Recall that in both cases the iterative procedure is applied to obtain an estimation ofα present in the scene under H 1 , see (16) and (28). In this light, both algorithms should be initialized with some non-iterative estimation ofα.…”
Section: Performance Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Existence and uniqueness of the above equation solution T F P , the Fixed Point (FP) estimate, have been investigated in [3], and its statistical properties (consistency, unbiasedness and asymptotic Gaussianity) have been studied in [4]. In practice, it is obtained by the associated recursive algorithm which converges whatever the initialization (see for details [3]).…”
Section: Statistical Frameworkmentioning
confidence: 99%